Democratic Manual for the Democratic National Convention of 1968 - Clarence Cannon:::::: (1968)
The official Democratic Manual for the Democratic National Convention of 1968, originally prepared by Clarence Cannon for the Democratic National Committee. It explains the structure, powers, and procedures of the Democratic National Committee, the Congressional and Senatorial Campaign Committees, and the National Convention itself. The manual details rules governing delegate selection, voting, the unit rule, convention committees, debates, nominations, and the handling of contests and credentials. It includes the formal call to the 1968 Democratic National Convention in Chicago, along with resolutions concerning delegate qualifications, voting rights, and the distribution of delegates and convention votes. The final section provides a historical record of past Democratic National Conventions, listing locations, nominees, and ballot totals for presidential and vice-presidential candidates.